Social Semiotics and Visual Grammar: A Contemporary Approach to Visual Text Research - Indro Moerdisuroso (Graduate School of Institut Seni Indonesia Yogyakarta, 2014)
This article outlines a visual text reading based on social semiotics approach, that is the visual grammar. It is an account of the explicit and implicit knowledge and practices around a resource, consisting of the elements and rules underlying a culture-specific form of visual communication. It required a general comprehension of social semiotics to obtain a deeply understanding to visual grammar. The differences between social semiotics and general semiotics expressed to accomplish its purpose. The concern of visual grammar is the relationship between ‘drawn participants’ and social life. Visual grammar can be positioned as a contemporary approach to visual texts meaning-making. Study of visual arts seems to entail visual grammar to play a more important role amid the phenomenon of visual culture that increasingly characterizes the lives of today’s society.